Synthesis and Characterization of Novel Organo-Inorganic Hybrid Material of Poly(3,4-Ethylene Dioxythiophene) and Phosphomolybdate Anion - A. Vadivel Murugan; C.-W. Kwon; G. Campet; B. B. Kale (Active and Passive Electronic Components)
The organo-inorganic hybrid material, consisting of Poly(3,4-Ethylene Dioxythiophene) (PEDOT) doped with phosphomolybdate cluster anions [PMo12O40]3− , has been synthesized by direct in situ oxidative polymerization of 3,4-Ethylene Dioxythiophene (EDOT) with phosphomolybdic acid (H3PMo12O40) . Its characterization is investigated by Fourier Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM). The hybrid material presents predominantly high electronic conductivities of around 2.0 and 7.0 S cm-1 at 300 and 400K respectively.